Pengaruh Sistem Informasi Akuntansi Sistem Pengendalian Internal dan Kompetensi Sumber Daya Mausia Terhadap Kualitas Laporan Keuangan pada Pusat Pengembangan Sumber Daya Manusia, Geologi Mineral dan Batubara Kota Bandung - Dwi Oktaviani, Mega; Devyanthi Syarif (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research was to investigate, using a descriptive and verification approach, the impact of Accounting Information Systems, Internal Control Systems, and Human Resource Competence on the Quality of Financial Reports. 42 individuals who received research samples from the Center for Human Resource Development, Mineral and Coal Geology, Bandung City, were given questionnaires as part of the data gathering process, which also involved fieldwork and library research. A quantitative approach was taken in this investigation. Using the Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Coefficient and Determination Coefficient, and hypothesis testing with the SPSS version 26 application, to quantify the extent of independent variables' partial and simultaneous influence on dependent variables. The findings demonstrated that the quality of financial reports was significantly impacted by the accounting information system, positively impacted by the internal control system, and negatively impacted by human resource competency. The Quality of Financial Reports was Affected by the Internal Control System, the Accounting Information System, and Human Resource Competence All at the Same Time.